Experimental validation of the design and control of a compressed air energy storage system - Rais, Ilham; Ed-dahmani, Chafik; Benami, Abdellah (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
In this paper, we introduce a comprehensive design and control strategy for an energy storage system based on compressed air to enhance both electrical energy quality and operational flexibility. The formulation of this control structure involved extensive calculations and computer simulations, which now require experimental validation. We describe the specifically designed test benches for this purpose and present an analysis of the experimental results. The paper begins with a brief overview of the didactic bench used to test the pure pneumatic conversion system, followed by the presentation and discussion of the initial practical results of the maximum energy point tracking (MEPT) strategy derived from this bench.